A Comparison of Two Repertory Grid Measures of Personal Construct Conflict - Christopher C. O'Lansen,; Ian T. Jones,; Samantha L. Horvath,; Eliwid Medellin,; Katie Maupin,; Hailey E. McDaniel-Johnson,; Emery K. Thackerson,; Megan Baker,; James W. Grice, (Advances in Social Sciences Research Journal, 2021)
Intrapersonal conflicts have long been recognized as potential contributors to negative psychological and emotional states. Using repertory grids personal construct psychologists have developed methods for identifying implicative dilemmas, a type of conflict that arises from incongruous constructions of a person’s actual and ideal selves. Recent studies have reported greater numbers of implicative dilemmas among clinical samples when compared to controls. Another approach to conceptualizing and measuring intrapsychic conflicts is Chambers’ coordinate grid procedure, a modified repertory grid technique that assesses logical inconsistencies within a person’s construct system. The purpose of this study was to investigate the relationship between implicative dilemmas and logical inconsistencies in a sample of college students. Previous studies have moreover reported positive associations between repertory grid measures of construct system conflict and standardized assessments of depression, anxiety, and self-esteem. These associations were also examined in this study. Results revealed no systematic relationship between implicative dilemmas and logical inconsistencies, and neither repertory grid index was associated with scores on the depression, anxiety, and self-esteem questionnaires. Actual-ideal self-discrepancies were found to be associated with self-esteem, however, and examination of two individual grids revealed the clinical utility of the repertory grid procedures.